Dynamics of optical solitons in higher-order Sasa-Satsuma equation - Yao, Shao-Wen; Akinyemi, Lanre; Mirzazadeh, Mohammad; İnç, Mustafa; Hosseini, Kamyar; Senol, Mehmet (Elsevier, 2021)
Higher order and multidimensional generalizations of the nonlinear Schrodinger equation are useful in a variety of applications. A generalized (3+1)-dimensional nonlinear Sasa-Satsuma equation is studied via the improved generalized Riccati equation mapping method and its Backlund transformation and the extended hyperbolic function method. This nonlinear model can be use to describe the physical processes of wave propagation in optical fibers. We explicitly retrieved varieties of optical solitons like bright, dark, singular, combined bright-dark and combined singular-bright to this multidimensional generalized nonlinear model. Other solutions, such as periodic, rational, and exponential solutions of different structures, are also produced as a result of the evolution of this improved technique. Furthermore, the graphs in two and three dimensions are provided to visualize the structure of the solutions acquired by choosing certain parameter values.
Keywords: Sasa-Satsuma equation; Extended hyperbolic function method; Optical solitons; Improved generalized Riccati equation mapping method; Backlund transformation